Joint association of triglyceride glucose index (TyG) and body roundness index with the risk of periodontitis: a cross-sectional study - Wang, Liang; Liu, Jia; Wang, Junjie; Liu, Pan; Zhao, Qin; Wang, Yu; Zhao, Hongyu; Zhu, Xiao; Liu, Shan; Zhang, Jinqiang (Frontiers in Nutrition, 2025)
BackgroundPeriodontitis is a prevalent chronic inflammatory non-infectious condition, primarily induced by subgingival bacteria. The aim of this study was to investigate the interaction between body roundness index (BRI) and TyG index on periodontitis and to explore whether the connection was associated with sex.Study designCross-sectional study.MethodsThis cross-sectional study included 261,454 participants between 2017 and 2024. The associations of the TyG index and BRI with periodontitis risk were investigated via logistic regression analysis and restricted cubic splines. Subgroup analysis was used to explore potential differences. A sensitivity analysis was conducted using multivariate regression to evaluate the associations between TyG-related indicators and periodontitis.ResultsAmong the 261,454 participants, 40,991 individuals were diagnosed with periodontitis. Individuals with high TyG and high BRI (TyG > 8.60 and BRI > 3.19) had the highest risk of developing periodontitis, suggesting a synergistic effect. Next, we multiplied these two metrics to establish TyG-BRI. TyG-BRI was nonlinearly positively correlated with the risk of periodontitis, with the highest quartile having a more significant effect on the risk of periodontitis compared to the lowest quartile (OR = 1.47; 95% CI: 1.40, 1.53). The TyG-BRI index had a significant effect on periodontitis in those less than 60 years of age, female, and non-smokers, and this effect was particularly prominent in women aged 30–50 years. Sensitivity analysis showed that the associations between the correlation indices (TyG index, BRI, and TyG-BRI) and periodontitis are statistically significant.ConclusionOverall, the TyG-BRI index can be used as a predictor of periodontitis risk. The link was strongest in individuals under 60 years, women, and non-smokers, suggesting potential roles of age-related metabolic changes, estrogen, and smoking-induced systemic inflammation in modulating this relationship. In the future, this mechanism needs to be further verified in combination with the levels of sex hormones.